2016
DOI: 10.1186/s13223-016-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic studies of atopic dermatitis

Abstract: BackgroundAtopic dermatitis (AD) is a chronic inflammatory disease caused by the complex interaction of genetic, immune and environmental factors. There have many recent discoveries involving the genetic and epigenetic studies of AD.MethodsA retrospective PubMed search was carried out from June 2009 to June 2016 using the terms “atopic dermatitis”, “association”, “eczema”, “gene”, “polymorphism”, “mutation”, “variant”, “genome wide association study”, “microarray” “gene profiling”, “RNA sequencing”, “epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(181 citation statements)
references
References 149 publications
3
172
0
6
Order By: Relevance
“…Recently, omalizumab (anti‐IgE Ab) treatment was shown to augment pDC IFNα responses and attenuate pDC FcεRI expression . Moreover, the promoter polymorphism of TLR9, which plays a pivotal role in IFNα production of pDCs, has been shown to have putative association with AD . Our results in this study which employed a protein‐patch murine model of EC sensitization are in agreement with these clinical data.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, omalizumab (anti‐IgE Ab) treatment was shown to augment pDC IFNα responses and attenuate pDC FcεRI expression . Moreover, the promoter polymorphism of TLR9, which plays a pivotal role in IFNα production of pDCs, has been shown to have putative association with AD . Our results in this study which employed a protein‐patch murine model of EC sensitization are in agreement with these clinical data.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is not very surprising that Genome Wide Association studies revealed that epidermal barrier defects, caused by dysfunction of important TJ or scaffolding proteins, are correlated with allergen sensitization in human diseases . In fact, a recent retrospective PubMed search study disclosed that the most significant risk factor for the development of AD is null mutations in the filaggrin ( Flg ) gene, which codes for a protein with multiple roles in the maintenance of epidermal barrier function . The importance of the epidermal barrier function in sensitization to allergens was emphasized by numerous experimental models where proteins involved in barrier integrity were genetically mutated [reviewed in ].…”
Section: Allergen Sensitization Via the Skin: More Than A Decreased Ementioning
confidence: 99%
“…Recently, there have been many discoveries involving the genetic and epigenetic studies of AD. Two major biological pathways are responsible for AD aetiology: skin barrier function and innate/adaptive immune responses . The dysfunctional epidermal barrier and immune response reciprocally affect each other and thereby drive development of AD .…”
Section: Introductionmentioning
confidence: 99%
“…Two major biological pathways are responsible for AD aetiology: skin barrier function and innate/adaptive immune responses . The dysfunctional epidermal barrier and immune response reciprocally affect each other and thereby drive development of AD . In terms of skin barrier function, variations in the filaggrin gene ( FLG ), serine protease inhibitor Kazal‐type 5 gene ( SPINK5 ) and serine protease Kallikrein 7 gene ( KLK7 ) have been identified to play roles .…”
Section: Introductionmentioning
confidence: 99%